Coupled heat and humidity control system of narrow-trough solar collector and solid desiccant in Chinese solar greenhouse: Analysis of optical / thermal characteristics and experimental study. (15th June 2023) - Chen, Xinge; Liang, Hao; Wu, Gang; Feng, Chaoqing; Tao, Tao; Ji, Yaning; Ma, Qianlei; Tong, Yuxin
Abstract: Taking Chinese solar greenhouse as the research object, a greenhouse heat and humidity control system combining Narrow-Trough Solar Collector (NTC) and solid desiccant is proposed in this paper. The system is a day and night double-cycle mode, which can realize multiple adsorption and desorption by using solid desiccant. On the basis of solar energy as the main energy supply, a sustainable regulation means is realized. The optical analysis and geometric relationship analysis are carried out. When the inclination angle of NTC is 30°, it can provide more than 80% optical efficiency in Beijing winter at 40° north latitude. The system can regulate the relative humidity of greenhouse at night from high humidity range to normal crop growth range in winter (94.2%–81.3%), the average relative humidity decreased by 12.9% and the indoor average temperature increased by 1.2 °C.The water removal rate of the system is 11.6 g/s m −2 . Combined with solar medium temperature heat collection technology and recyclable solid desiccant, the temperature and humidity environment in the solar greenhouse in winter is adjusted to the appropriate range for crop growth. Highlights: A heat and humidity control system of solar greenhouse with solid desiccant was proposed. The thermal and optical characteristics of the narrow-trough collector in the system are analyzed. The average dehumidification rate per unit area of the system is 11.6 g/s · m −2 . The average relative humidity at night in the test greenhouse decreased from 94.2% to 81.3%.